Dissect the DNMT3A- and DNMT3B-mediated DNA Co-methylation through a Covalent Complex Approach. Issue 2 (17th January 2020) - Gao, Linfeng; Anteneh, Hiwot; Song, Jikui
Abstract: DNA methylation plays a critical role in regulating gene expression, genomic stability, and cell fate commitment. Mammalian DNA methylation, which mostly occurs in the context of CpG dinucleotide, is installed by two de novo DNA methyltransferases, DNMT3A and DNMT3B. Oligomerization of DNMT3A and DNMT3B permits both enzymes to comethylate two CpG sites located on the same DNA substrates. However, how DNMT3A- and DNMT3B-mediated co-methylation contributes to the DNA methylation patterns remain unclear. Here we generated covalent enzyme–substrate complexes of DNMT3A and DNMT3B, and performed bisulfite sequencing-based single-turnover methylation analysis on both complexes. Our results showed that both DNMT3A- and DNMT3B-mediated co-methylation preferentially gives rise to a methylation spacing of 14 base pairs, consistent with the previous structural observation for DNMT3A in complex with regulatory protein DNMT3L and CpG DNA. This study provides a novel method for mechanistic investigation of DNMT3A- and DNMT3B-mediated DNA co-methylation. Graphical abstract: Image 1 Highlights: Formation of covalent complexes between DNMT3A/3B and DNA. The method performs enzymatic assays with covalent complexes of DNMT3A/3B. Accurate measurement of single-turnover methylation event was developed. DNMT3A/3B comethylates CpG DNA with preferred 14-bp spacing.